CD146-targeted nuclear medicine imaging in cancer state of the art - Yang, Qi (View (Beijing, China), 2023)
The transmembrane glycoprotein adhesion molecule CD146 is overexpressed in a wide variety of cancers. Through molecular imaging, a specific biomarker's expression and distribution can be viewed in vivo non-invasively. Radionuclide-labeled monoclonal antibodies or relevant fragments that target CD146 may find potential applications in cancer imaging, thereby offering tremendous value in cancer diagnosis, staging, prognosis evaluation, and prediction of drug resistance. This review discusses the recent developments of CD146-targeted molecular imaging via nuclear medicine, especially in malignant melanoma, brain tumor, lung cancer, liver cancer, breast cancer, and pancreatic cancer. Many studies have proved that CD146 targeting may present a promising strategy for cancer theranostics